การปรับใช้ภูมิปัญญาท้องถิ่นด้านการแพทย์แผนไทยเพื่อสนับสนุนการท่องเที่ยว โดยชุมชน กรณีศึกษา สวนสมุนไพรแอนนี่ อําเภอโพธิ์ไทร จังหวัดอุบลราชธานี - บุญประสม นวพร (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2015)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) เพื่อสํารวจบริบทภูมิปัญญาท้องถิ่นด้านการแพทย์แผน ไทยของสวนสมุนไพรแอนนี่ อําเภอโพธิ์ไทร จังหวัดอุบลราชธานี 2) เพื่อนําภูมิปัญญาท้องถิ่นด้าน การแพทย์แผนไทย มาสร้างผลิตภัณฑ์ทางการท่องเที่ยวเชิงสุขภาพโดยชุมชน โดยเครื่องมือที่ใช้ในการ เก็บรวมรวบข้อมูล คือ แบบสํารวจภูมิทัศน์วัฒนธรรม (Cultural landscape) ในการสํารวจบริบทภูมิ ปัญญาท้องถิ่นด้านการแพทย์แผนไทยของสวนสมุนไพรแอนนี่ อําเภอโพธิ์ไทร จังหวัดอุบลราชธานีและ นําแบบสัมภาษณ์แบบมีโครงสร้าง โดยการสัมภาษณ์แบบเจาะลึกเป็นรายบุคคล เพื่อใช้ศึกษาภูมิปัญญา ท้องถิ่นด้านการแพทย์แผนไทยสวนสมุนไพรแอนนี่ และส่วนอื่น ๆ ที่เกี่ยวข้องกับการท่องเที่ยวภายใน ชุมชน จากนั้นนําผลการศึกษาจากวัตถุประสงค์ข้อที่ 1 และ 2 มาทําการวิเคราะห์และสังเคราะห์ตาม หลักการและเหตุผล ตรงตามแนวคิด ทฤษฎี และข้อเท็จจริงที่ทําการศึกษาจากนั้นนําเสนอผลการศึกษา เป็นผลิตภัณฑ์ทางการท่องเที่ยว โดยการพรรณนาวิเคราะห์ (Descriptive) ผลการศึกษาพบว่า ภูมิปัญญาท้องถิ่นด้านการแพทย์แผนไทยและกิจกรรมการท่องเที่ยวที่ สามารถนํามาสร้างเป็นผลิตภัณฑ์ทางการท่องเที่ยวที่น่าสนใจได้ดังนี้คือ พื้นที่ของสวนสมุนไพรแอนนี่ บ้านนานางวาน ตําบลม่วงใหญ่ อําเภอโพธิ์ไทร จังหวัดอุบลราชธานี โดยภายในสวนมีสมุนไพรที่ รวบรวมไว้ประมาน 1,000 กว่าชนิด บนเนื้อที่กว่า 100 ไร่ ที่สามารถให้ความรู้และการรักษาโรคด้วย พืชสมุนไพร และในแต่ละครัวเรือนจะปลูกพืชสมุนไพรใช้กันในครัวเรือน ซึ่งเป็นไปตามหลักความเชื่อ ของชาวอีสานที่มักใช้สิ่งที่มีอยู่ภายในท้องถิ่นรักษาอาการเจ็บป่วยของตน จากการสัมภาษณ์ทําให้ทราบ ถึงวิถีชีวิตความเป็นอยู่ที่เรียบง่ายส่วนใหญ่นิยมใช้วัตถุดิบในชุมชนมาใช้ในชีวิตประจําวัน และมี ทรัพยากรทางการท่องเที่ยวที่น่าสนใจในบริเวณใกล้เคียง อาทิเช่น สามพันโบก และ หาดสลึง ซึ่งใน ปัจจุบันชุมชนมีแหล่งท่องเที่ยวที่ดึงดูดให้นักท่องเที่ยวเข้ามาเยี่ยมชม ไม่ว่าจะเป็นธรรมชาติ วิถีชีวิตของ คนในชุมชน มีสวนสมุนไพรให้เกิดการเรียนรู้ และวิธีการในการดูแลรักษาสุขภาพอย่างถูกต้องจาก ปราชญ์ผู้มีความรู้ในชุมชนอยู่แล้ว อาจมีการพัฒนาสภาพภูมิทัศน์โดยรอบ เพื่อทําให้มีความสะดวกใน การเดินทางเข้าสู่ชุมชน ปรับปรุงให้มีความสวยงามและเกิดความปลอดภัยมากยิ่งขึ้น รวมถึงการ ปรับปรุงสาธารณูปโภคขั้นพื้นฐาน เพื่ออํานวยความสะดวกให้แก่นักท่องเที่ยว ในอนาคตการเพิ่ม จํานวนที่พักแรม โดยสนับสนุนที่พักแบบโฮมสเตย์ เพื่อให้คนในชุมชนมีส่วนร่วมในการจัดการท่องเที่ยว มากที่สุด การสร้างรูปแบบในการจัดกิจกรรมเพื่อการท่องเที่ยว โดยชุมชนที่เหมาะสม ควรสร้างให้เกิด การเรียนรู้ร่วมกันระหว่างนักท่องเที่ยวและผู้มาเยือนช่วยกันสืบทอดภูมิปัญญาท้องถิ่นไว้ร่วมกัน ทั้งนี้ สามารถนําภูมิปัญญาท้องถิ่นด้านการแพทย์แผนไทย มาสร้างผลิตภัณฑ์ทางการท่องเที่ยวเชิงสุขภาพ โดยชุมชน โดยผู้วิจัยได้นําเสนอ ผลิตภัณฑ์ทางการท่องเที่ยว เป็นโปรแกรมการเดินทางท่องเที่ยวเชิง สุขภาพโดยชุมชน แบ่งออกเป็น 2 แบบคือ การบริการแบบไม่ค้างคืน (ไป-กลับ) และการบริการแบบ ค้างคืนเพื่อเป็นตัวเลือกให้แก่นักท่องเที่ยวที่สนใจในการเดินทางท่องเที่ยวและการดูแลสุขภาพไปพร้อม กัน Abstract The purposes of this research were to 1) survey the contexts of local wisdom on Thai traditional medicine of Anny Herbs Garden, Pho Sai District, Ubon Ratchathani Province, 2) bring the local wisdom on Thai traditional medicine to make the health tourism products by the community. The instrument used for data collection was the survey model of cultural landscape from National Park Service, America, both subjective and objective aspect for surveying the contexts of local wisdom on Thai traditional medicine of Anny Herbs Garden, Pho Sai District, Ubon Ratchathani Province. The structured interview and individual in-depth interview were used for studying the local wisdom on Thai traditional medicine of Anny Herbs Garden and other parts related to the tourism within the community of Pho Sai District, Ubon Ratchathani Province. The interview form consisted of 3 parts which included Part 1) general information of the responders, Part 2) information of community contexts on tourism resources, tourism situations of Muang Yai Sub-district community, Pho Sai District, Ubon Ratchathani Province, and Part 3) additional recommendation. The results of the purposes 1 and 2 were analyzed and synthesized pursuant to the principles and reasons in accordance with the concepts, theories and facts studied. The study results were proposed as the tourism products by descriptive analysis. The research results revealed that the local wisdom of Thai traditional medicine and tourism activities which could be created as the interesting tourism products were as follows: the area of Anny Herbs Garden of Ban Nanangwan, Muang Yai District, Pho Sai District, Ubon Ratchathani Province, there were more than 1,000 kinds of herbs garden around over 100 Rai areas, where could provide knowledges and herbal treatment. The herbs were grown for use in each household. This was in accordance with the belief of I-san people who usually applied existed things in the locality to treat their illness. According to the interview, it was indicated that most of the people lived simply by using materials available in the community for their use in daily life. Moreover, there were interesting tourism resources in the areas nearby, such as Sampanbok, Saleung Beach, etc. Currently, there are tourism resources attracting the tourists to visit in terms of nature, local life of people in the community, herbs garden for learning, correct methods of health care from local scholars. Moreover, it may have the development of landscape surrounded to make convenient for travelling to the community, improve the environments of community to be more beautiful and safer as well as improving the basic public utilities to facilitate the tourists. In the future, the residents will be increased by homestay quantity to support community people to participate in the tourism management the most. For creating the appropriate tourism activities model by community, it should create the model which supports mutual learning for the tourists and visitors to inherit local wisdom. For bringing the local wisdom of Thai traditional medicine to create the health tourism products by community, the researcher proposed the health tourism products by the community for 2 types including the day care service and overnight service as the choice for interested tourists who preferred both tourism and health care.